2015
DOI: 10.1017/s0954579414001394
|View full text |Cite
|
Sign up to set email alerts
|

The effects of violence exposure on the development of impulse control and future orientation across adolescence and early adulthood: Time-specific and generalized effects in a sample of juvenile offenders

Abstract: Impulse control and future orientation increase across adolescence, but little is known about how contextual factors shape the development of these capacities. The present study investigates how stress exposure, operationalized as exposure to violence, alters the developmental pattern of impulse control and future orientation across adolescence and early adulthood. In a sample of 1,354 serious juvenile offenders, higher exposure to violence was associated with lower levels of future orientation at age 15 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…50,51 Research has also shown that witnessing violence may disrupt children’s development of self-regulatory capacities resulting in greater difficulties with impulse control and emotional and behavioral dysregulation. 12,47,52 Such self-regulation difficulties are a hallmark of multiple mental health problems. 53 The present study adds to this literature by examining the association between witnessing community violence and parallel patterns of aggression and impulsivity across adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Research has also shown that witnessing violence may disrupt children’s development of self-regulatory capacities resulting in greater difficulties with impulse control and emotional and behavioral dysregulation. 12,47,52 Such self-regulation difficulties are a hallmark of multiple mental health problems. 53 The present study adds to this literature by examining the association between witnessing community violence and parallel patterns of aggression and impulsivity across adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Romer (2010) noted several aversive childhood experiences (e.g., physical and emotional abuse) may impact risk-taking propensity generally, and other factors (e.g., peer influences) may shape the development of sensation seeking (and ostensibly other personality characteristics) through selection and socialization processes. Prior research has also suggested that contextual factors (such as exposure to violence, stress and parenting) may shape the development of impulsivity during adolescence (King, Lengua, & Monahan, 2013; Monahan, King, Shulman, Cauffman & Chassin, in press). Given the current results, future research should explore factors that may account for the overlap in individual differences in change across facets of related to disinhibition and impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the consequences of AOD use are likely to resonate across the period of emerging adulthood, but we know little about how, if at all, AOD use etiology varies across this important developmental transition. Researchers have shown both that (1) the psychological effects of violence exposure depend on the timing of the exposure (Monahan, King, Shulman, Cauffman, & Chassin, 2015); and that (2) both AOD use (SAMHSA, 2013) and violence exposure (Loeber & Farrington, 2012;Resnick et al, 2004;Stoddard et al, 2015;Sullivan et al, 2006) change with age. Yet, age specificity in the link between violence exposure and AOD use and how this age specificity depends on the type of violence exposure has not been studied.…”
Section: Adolescence and Emerging Adulthoodmentioning
confidence: 99%